An Integrated Energy Economic Interaction Model with Application to Egypt - Rady, Yassin Yehia (AUC Knowledge Fountain, 2019)
Traditional bottom-up energy models have been widely applied to date to assess the impact of the future energy technologies over a specific time horizon, quantifying the direct economic and environmental implications caused by the evolution of the energy sector. However, such approaches ignore the interactions that the energy sector has with other sectors in the economy, hence failing in quantifying the global impact associated with their technologies: this may produce an unfortunate bias in the definition of future energy and environmental policies. The present study assesses, on a nationwide economy scale, the economic and environmental impacts due to the optimal future power generation mix in Egypt, by soft-linking a bottom-up, technology-rich model (OSeMOSYS) with a top-down Input-Output Analysis model (IOA, based on the EORA 26 dataset). Based on the OSeMOSYS energy modeling framework, the OSeMOSYS-Egypt model is developed. The least cost power generation mix is determined for two different electricity demand forecasts, based on both the New Policies demand forecast scenario developed by International Energy Agency and the market research performed by Business Monitor International. The robustness of the obtained results is assessed through a sensitivity analysis on the main exogenous parameters, including costs, efficiency and production targets of energy technologies, capital discount rate, water and natural gas resources availability. The evolution of the Egyptian power sector in years 2018 to 2040 is analyzed: results of the bottom-up energy model are adopted as exogenous parameters to the top-down multi-sector model, as a way of coupling the two aforementioned models. It is revealed that Combined Cycles, Wind, and Photovoltaic rooftop systems are viable technologies that should be considered in the future Egypt’s power generation mix. In particular, among Egypt’s abundant renewable energy resources, it is shown that wind power technology comes first in achieving the proposed target on renewables penetration in the country’s generation mix, and it might be a feasible alternative to replace part of the natural gas share. To increase the accuracy of the analysis, the original OSeMOSYS framework has been enhanced by imposing the discount rate on capital investments for the energy technologies, as a time dependent exogenous variable; in developing countries in general and in Egypt in particular, discount rates have been known to fluctuate widely. The derived power generation mix, predicted by the bottom-up model, has been applied to the IOA model in the form of a change in energy technology mix and a change in final demand of electricity. To account for the growth in the national GDP during the temporal planning horizon, an econometric function that relates the growth in GDP to increase in the production of electricity is formulated. Besides the results of the energy model, this approach enables the decision maker to assess the expected primary energy requirements, GHG emissions and water use induced by the evolution of the energy mix in a broader perspective. It is worth to note that, the results of the bottom-up energy optimization model indicates that the anticipated increase in the penetration of renewables in the power generation mix, would decrease the primary non-renewable energy consumption and GHG emissions directly caused by the power generation sector over the considered temporal planning horizon (2018-2040). However, the application of the IOA model reveals that decarbonizing the power sector alone is not sufficient in achieving neither, the decoupling of the GDP growth and the total primary energy consumption, nor the GHG emissions within the Egyptian economy.